Efficacy estimation of a combination of triple antimicrobial agents against clinical isolates of Mycobacterium abscessus subsp. abscessus in vitro. Issue 1 (19th February 2021) - Asami, Takahiro; Aono, Akio; Chikamatsu, Kinuyo; Igarashi, Yuriko; Morishige, Yuta; Murase, Yoshiro; Yamada, Hiroyuki; Takaki, Akiko; Mitarai, Satoshi
Abstract: Background: Mycobacterium abscessus subsp. abscessus ( M. abscessus ) is a rapidly growing mycobacterium that is resistant to most antibiotics. The number of patients with pulmonary disease caused by M. abscessus is increasing in several regions, and therapy involves long-term antibiotic combination treatments, although no standard treatment regimen has been established. Objectives: To examine candidate regimens for maintenance of antimicrobial treatment against M. abscessus by measuring MIC using the three-drug chequerboard method. Methods: We evaluated the drug susceptibility of 70 clinical isolates of M. abscessus using the three-drug chequerboard method. We tested the antimycobacterial agents bedaquiline, clofazimine, amikacin, and sitafloxacin (which showed a relatively low MIC range when used as single agents) alone and in combinations. Results: The three-drug combinations of bedaquiline/clofazimine/amikacin, and bedaquiline/clofazimine/sitafloxacin were studied. Among isolates for which the fractional inhibitory concentration index (FICI) could be calculated, 29/70 isolates (41%) and 11/70 isolates (16%) showed a synergistic response (FICI ≤0.75) with combined use of bedaquiline/clofazimine/amikacin, or with bedaquiline/clofazimine/sitafloxacin, respectively. Conclusions: The combination of bedaquiline with clofazimine plus either amikacin or sitafloxacin may be useful as maintenance regimens when treating pulmonary disease caused by M. abscessus .